Socioeconomic status and reading outcomes: Neurobiological and behavioral correlates. Issue 183 (22nd July 2022) - Romeo, Rachel R.; Uchida, Lili; Christodoulou, Joanna A.
Abstract: In this chapter, we examine reading outcomes and socioeconomic status (SES) using a developmental cognitive and educational neuroscience perspective. Our focus is on reading achievement and intervention outcomes for students from lower SES backgrounds who struggle with reading. Socioeconomic disadvantage is a specific type of vulnerability students experience, which is often narrowly defined based on parental income, education level, and/or occupational prestige. However, implications of socioeconomic status extend broadly to a suite of areas relevant for reading outcomes including a student's access to resources, experiences, language exposure, academic outcomes, and psychological correlates. Underlying this constellation of factors are brain systems supporting the processing of oral and written language as well as stress‐related factors. We review the implications of SES and reading achievement, and their intersectionality, for the science and practice of reading instruction.